Performance strategies of Greek track and field athletes: Gender and level differences - Katsikas, C.; Argeitaki, P.; Smirniotou, A. (Biology of Exercise, 2009)
Psychological skills play an important role in athletic performance. The aim of the present study was to examine possible differences in the use of psychological skills of Greek track and field athletes of different gender and level. The sample consisted of 364 track and field athletes (241 males, 123 females), aged 18.9 ± 3.9 years, with different level (elite - non elite). The Test of Performance Strategies (TOPS) was used. The participants completed the TOPS questionnaire during the precompetitive period. The results showed that elite level athletes were significantly better compared to non elite in emotional control, goal setting, imagery, activation, negative thinking and relaxation. Also, male athletes had better emotional control and used more relaxation, compared to females. Among elite level athletes, gender differences in psychological skills remained, with females displaying less effective emotional control and relaxation. The differences between athletes of different gender and level could be considered from coaches and sport psychologists in order to help athletes improve their athletic performance.